The Paradigms of Higher Education in Pekanbaru Towards the Inheritance of Traditional Riau Malay Dance - Evadila Evadila; Hartono Hartono; Warih Handayaningrum; Eko Sugiarto (Universitas Negeri Semarang, 2023)
Modernization, the invasion of immigrants and local migrants, and technology have influenced the younger generation's interest in traditional dance. Universities in Pekanbaru have played an important role in preserving and passing down the Traditional Riau Malay Dance . In the 1970s, higher education institutions in Riau began to contribute to Malay art and culture. This is an effort to rediscover Riau's Malay heritage which has begun to wane in demand. This study aims to analyze the paradigm of higher education in Pekanbaru related to the heritage of Traditional Riau Malay Dance . The exploratory interpretative literature research method employed is this study. The results showed that tertiary institutions have three different but interrelated paradigms in maintaining the continuity of traditional Riau Malay culture through dance. Firstly, the paradigm of formal education through lectures with traditional Riau Malay dance. Secondly, informal education through art communities in higher education environments that have student activity units in the form of a dance studio, the Kompang music community. facilitating community members to learn from each other and develop their skills in dancing and playing traditional music. Thirdly, the paradigm through cultural education is related to the development of students' talents and creativity in the arts, creative education is carried out through activities including workshops, seminars and art performances on and off campus. These three paradigms are then integrated into the Higher Education curriculum. The paradigms are useful for the preservation of traditional Riau Malay dances along with increasingly modern developments.